Maldives : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Maldives. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation discusses that growth in Maldives has been strong and is projected to remain so in 2019 driven by tourism, commerce, and construction. Nonetheless, the Maldives remains highly vulnerable with reduced policy space due to large and growing public debt and rising pressures on external stability. The consultation focused on addressing external imbalances including offering advice on restoring fiscal buffers, strengthening public finance management, reforming the exchange rate regime, building international reserves, improving governance, implementing structural reforms, and encouraging diversification. The outlook is for continued strong growth and moderate inflation, and only a gradual improvement in fiscal and current account deficits. As major infrastructure projects will gradually start to unwind, the current account deficit will begin to narrow. Under the current policies, the fiscal deficit is projected to remain elevated. However, successful implementation of tax reforms and improved tax administration, together with measures to contain budgetary spending, would result in a narrowing of both fiscal and current account deficits and mitigate the risks posed by high and rising public and external debt.